The usability evaluation of website interface for mobile commerce website. (2015) - Ou, Tsung-Yin; Perng, Chyuan; Hsu, Shih-Peng; Chiou, Wen-Chih
Mobile network creates an environment that is convenient with fast communication and no localisation restriction in which it is a perfect network environment for mobile commerce websites in developing business information applications and services. Consumers decide to leave or stay on the website not only depending on the quality of the services, but also consider the usability of the website which will be the crucial factor. This study focused on how website can offer better usability to consumer with higher efficiency, effectiveness, learnability and memorability. Experimental questionnaire has been used to evaluate the usability in different mobile websites. The results showed that there are significant differences between different websites in effectiveness and learnability. It also found that 'registration process' at Yahoo! Shopping Mall's cause confusion for many users during the shopping procedure. This study proposed several suggestions for mobile website to improve the usability after analysing the problems.